2022
DOI: 10.1371/journal.pone.0269787
|View full text |Cite
|
Sign up to set email alerts
|

The structural changes of gray matter in Parkinson disease patients with mild cognitive impairments

Abstract: Objectives Parkinson disease (PD) is associated with cognitive impairments. However, the underlying neural mechanism of cognitive impairments in PD is still not clear. This study aimed to investigate the anatomic alternations of gray matter in PD patients with mild cognitive impairment (MCI) and their associations with neurocognitive measurements. Methods T1-weighted magnetic resonance imaging (MRI) data were acquired from 23 PD patients with MCI, 23 PD patients without MCI, and 23 matched healthy controls. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 81 publications
(77 reference statements)
1
8
1
Order By: Relevance
“…First, the direct comparison between HC and PD groups showed a significant gray matter volume difference between the two groups in a widespread bilateral network, covering especially frontal areas but also left cingulate cortex, bilateral parietal areas as well as occipital cortices. These findings are in line with previous cross-sectional studies describing a distributed pattern of structural reductions of gray matter in PD (see Xu et al, 2020, for a meta-analysis) related to neurocognitive dysfunctions (Li et al, 2022) and morphometric longitudinal imaging studies which report significantly greater annual brain volume loss in patients with PD compared to control subjects (Hu et al, 2001). In particular, frontal lobe atrophy associated with the duration of motor symptoms was described in late-onset PD (Double et al, 1996), and frontal lobe changes were found in patients with PD who had mild cognitive impairment and in those with dementia (Beyer et al, 2007;Burton et al, 2004), and This document is copyrighted by the American Psychological Association or one of its allied publishers.…”
Section: Discussionsupporting
confidence: 92%
“…First, the direct comparison between HC and PD groups showed a significant gray matter volume difference between the two groups in a widespread bilateral network, covering especially frontal areas but also left cingulate cortex, bilateral parietal areas as well as occipital cortices. These findings are in line with previous cross-sectional studies describing a distributed pattern of structural reductions of gray matter in PD (see Xu et al, 2020, for a meta-analysis) related to neurocognitive dysfunctions (Li et al, 2022) and morphometric longitudinal imaging studies which report significantly greater annual brain volume loss in patients with PD compared to control subjects (Hu et al, 2001). In particular, frontal lobe atrophy associated with the duration of motor symptoms was described in late-onset PD (Double et al, 1996), and frontal lobe changes were found in patients with PD who had mild cognitive impairment and in those with dementia (Beyer et al, 2007;Burton et al, 2004), and This document is copyrighted by the American Psychological Association or one of its allied publishers.…”
Section: Discussionsupporting
confidence: 92%
“…Nevertheless, increased cerebellar glucose metabolism has consistently been observed in the literature in cognitively impaired PD patients 29,30 , which has often been hypothesized to be related with compensatory mechanisms. Previous VBM studies have revealed that PD-MCI patients had a drastic GM decrease in the right insula, right inferior frontal gyrus middle frontal gyrus), and right cerebellum regions in comparison to PD patients who were cognitively healthy 31 . In this study, we observed an increase in GM within the cerebellum of PD-UHC patients compared to PD-SHC, even before they exhibited noticeable cognitive symptoms.…”
Section: Discussionmentioning
confidence: 91%
“…This reduction extended from the frontal lobe, which was closely associated with cognitive function, to the cerebellum. Furthermore, the subcortical cerebellum area could serve as a neural biomarker to distinguish between HC, PD patients with MCI and PD patients without MCI [35]. Previous studies have demonstrated the discriminative power of the cerebellum as a feature in SVM to classify PD patients and different subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…These aberrant brain regions including the basal ganglia, visual network, and auditory network, have provided morphological evidence for the pathophysiology of PD [34]. A recent study which combined VBM and surface-based morphometry (SBM) in PD patients with mild cognitive impairments (MCI) showed reduced gray matter volume in the frontal cortex, extending to the cerebellum, and cortical thinning in the temporal lobes, extending to the parietal cortex [35]. Further substantiating the association between PD and alterations in brain structure, morphometric analysis focused on subcortical and cortical regions may serve as important biomarkers for disease progression in PD patients.…”
Section: Introductionmentioning
confidence: 99%